PENERAPAN PRINSIP TRANSPARANSI DAN MANAJEMEN PELAYANAN INFORMASI PUBLIK KOTA MEDAN DI DINAS KOMINFO - Patricia Herpayanti Rajagukgkuk; Gabriel Hutagaol; Jonson Rajagukguk; Maringan Panjaitan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Good governance can be understood by imposing characteristics, namely participation, law enforcement, transparency, equality of responsiveness, future insight, accountability, supervision, efficiency and effectiveness. But what you want to discuss is information transparency. Information transparency is openness in carrying out decision making and openness in expressing material and relevant information about the company. While transparency is the principle that guarantees access or freedom for everyone to obtain information about the administration of government and other activities, namely information about policies, the process of making, and the implementation and results achieved. This study uses a descriptive qualitative research method using interview and observation techniques. The study used "key informants, key informants and additional informants. The results of this study explain that the Implementation of the Transparency Principle in public service is good, it can be seen from the level of Service, Satisfaction, Clarity in providing information. Where the Head of the Office, Secretary and the community have established good cooperation in providing information in the community. So that it can be said that the provision of information to the people in Medan City is good and helps the community. KOMINFO's official office has suggestions, namely the Sekrel car and the official website that is used to provide information and community complaints so that the KOMINFO Office can receive public complaints and immediately follow up on complaints and immediately develop reports from the community and fix them.